SENYAWA PENCEMAR ORGANIK YANG PERSISTEN (POPs): PENGERTIAN, JENIS, KARAKTERISTIK, DAN PERKEMBANGANNYA DI INDONESIA - Ita Wulandari; Dede Falahudin (OSEANA, 2020)
Persistent organic pollutants (POPs) have been identified as representing a serious threat to the marine environment and received formal attention by nations worldwide including Indonesia as one of the signatories and ratified countries for the Stockholm Convention. Due to their emerging issues, the study of POPs at all aspects is needed. Therefore, this paper attempts to review characteristics and toxicological properties of POPs, the current status of POPs National Implementation Plans (NIPs) in Indonesia, and propose future directions of POPs study in Indonesia from basic research such as monitoring of POPs distribution in Indonesian seas to applied research for example study of POPs alternative compounds.